DIPLOMASI PUBLIK JEPANG DALAM MENINGKATKAN KUNJUNGAN WISATAWAN ASING MELALUI PENYELENGGARAAN OLIMPIADE TOKYO 2020 - Faishal Muhammad Dzulfiqar, (2023)
This study aims to discuss Japan's Public Diplomacy in increasing foreign tourist visits through the Tokyo 2020 Olympics. The main concept used in this study is the use of soft power assets and public diplomacy which divides its activities into three dimensions, namely news management, strategic communications, and relationship building. The method used in this study is descriptive analytical qualitative by going through four stages of data analysis, namely data reduction, data presentation and drawing conclusions/verification. The final results of this study show that the Tokyo 2020 Olympics as one of the international sports mega-events can be used as a medium for public diplomacy in spreading the important message that Japan wants to convey. In this case, Japan has a big goal to increase its tourism After the Covid-19 Pandemic so that the Tokyo 2020 Olympics which presents a massive amount of public participation from various parts of the world must be used effectively by Japan to attract global public interest to visit Japan.